Epistemologi Tafsir Al-Amthal Fitafsir Kitab Allah Al-Munzal Karya Nasir Makarim Al-Shirazi - Abdul Khamid (Jurnal Syntax Transformation, 2020)
A review of the epistemology of al-Amthal Tafsir is very important. This is to determine how interpretation essence (characteristics and aim of interpretation), interpretation source, and how method and validity of interpretation. As comprehensive tafsir with sosiology approach, this creation has non-ideological characteristics that is not displaying dissent among some schools of jurisprudence. This al-Amthal Tafsir is also book of Shi>’ah Ima>miyyah Ithna ‘Ashariyyah commentaries. With descriptive-analytic study, this paper finds that al-Amthal Tafsir epistemology base is sourced on Alquran and reason (individual interpretation and judgement) and this reason is more dominant of the Alquran and al-h}adi>th. al-Amthal Tafsir was composed by Na>s}ir Maka>rim al-Shira>zi. Based on the review of his resume, this paper proves that al-Amthal Tafsir is representation in which the author associates and responds to the problems that happened at that era and answers based on the era.